Pertanggungjawaban Yayasan Terhadap Tidak Terlaksananya Kewajiban Audit Laporan Keuangan oleh Akuntan Publik - Pemayun, Cokorde Trisna Dewi; Laksmi Dewi, Cokorde Istri Dian (Belom Bahadat, 2024)
The legal body of the educational foundation is a private legal body. Foundation wealth management and financial reporting must be done through appropriate strategies, considering applicable provisions and using information technology to support openness. An audit of the foundation's financial statements must be carried out to ensure that the financial report is prepared in a reasonable and correct manner and has sufficient evidence as a basis for its preparation. This study is a normative jurisprudential study that examines the liability of the foundation for non-execution of the obligation of auditing financial statements by the public accountant. Failure to carry out the audit of public accountants on the financial report of the educational foundation that meets the criteria as referred to in the Law of the Republic of Indonesia No. 28 Year 2004 On Amendments to the Law No. 16 Year 2001 On the Foundation entails legal consequences in the form of inspection of the Foundation. If the annual report documents are found to be incorrect and misleading, then the foundation's administrator and supervisor shall be liable to the injured party.